Can strength training modulate inflammatory markers in postmenopausal women with overweight and obesity? Evidence from a 12-week quasi-experimental study - Liang Tan; Kinga Agnieszka Humińska-Lisowska; Monika Helena Sawczyn; Ewelina Perzanowska; Zbigniew Ossowski (Complementary Therapies in Medicine, 2025)
Background: Many postmenopausal women with overweight and obesity are in a state of low-level chronic inflammation for a long period. This inflammatory state makes them vulnerable to a variety of chronic diseases. Exercise is an important complementary modality for managing inflammation. However, the effect of strength training (ST) on inflammatory markers is controversial. Therefore, this study aimed to investigate the effects of strength training on inflammatory markers in postmenopausal women. Methods: This quasi-experimental study assigned 48 postmenopausal women with overweight/obesity to either a Strength Training group (SG, n = 24) or a Daily Activity group (DG, n = 24). The SG underwent exercise intervention 3 times a week for 12 weeks, and the DG kept their daily life habits unchanged. Serum C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and adiponectin were measured before and after each intervention. Results: After the 12-week ST intervention, a repeated ANOVA showed that CRP (F=16.85, P < 0.001, Partial η²=0.26), TNF-α (F=13.28, P < 0.001, Partial η²=0.22), and in terms of adiponectin (F=5.45, P = 0.02, Partial η²=0.106) There was a significant group × time interaction effect. CRP levels in the SG decreased by 21.30 % compared to the pre (1.69 ± 0.41 vs. 1.33 ± 0.29), which was statistically significant compared to the DG (P < 0.01); TNF-α levels in the SG showed a significant difference compared to the DG (P < 0.01), but within-group analysis showed that there was no significant difference in TNF-α from baseline ( P > 0.05); In the SG, the levels of IL-6 and adiponectin did not show statistically significant differences compared to the DG (P > 0.05). However, adiponectin was significantly decreased in DG (p < 0.01). Conclusions: A 12-week ST intervention significantly decreases CRP levels in postmenopausal women with overweight and obesity; there may have been an inhibitory effect on the rise in TNF-α levels; the modulatory effects on IL-6 are not statistically significant; there may have been an inhibitory effect on the decrease in adiponectin levels. In future studies, dietary habits could be considered in combination with other lifestyle factors to explore the potential impact of these combined interventions on markers of inflammation in postmenopausal women with overweight and obesity.